SEKOLAH CINTA LINGKUNGAN : EDUKASI DAN AKSI DAUR ULANG SAMPAH DI SD NEGERI MANDIRI JAYA SERTA PENGADAAN TEMPAT SAMPAH DAN PAPAN EDUKASI - Eni Setianingsih; Tellymalvika; Felomena Marselina Wemaf; Firmansyah (Adiba Aisha Amira, 2025)
The increasing amount of waste has become a serious problem in Indonesia due to the habit of littering and the government's suboptimal handling of the issue. At SD Negeri Mandiri Jaya, the lack of facilities and a culture of waste sorting remains a challenge. Therefore, the School Loves the Environment programme was implemented, which included socialisation, the provision of separate waste bins, and educational boards to encourage students to maintain cleanliness and care for the environment. The objectives of this study were to improve the understanding of students at SD Negeri Mandiri Jaya about the types, sources, and impacts of waste, equip them with recycling skills, and provide supporting facilities such as separate waste bins and educational boards to foster a culture of environmental awareness from an early age. The research method used was educational socialisation and waste recycling activities through a participatory approach. The results of the study show that educational socialisation and waste recycling activities at SD Negeri Mandiri Jaya are strategic steps in fostering environmental awareness from an early age. Through the delivery of material, recycling practices, the provision of separate waste bins, and the installation of educational boards, students not only understand the importance of waste management but also become accustomed to practising it. This programme has a positive impact on school cleanliness, shapes environmentally conscious character, and supports the government's programme in education- and community-based waste management.